A prospective case–cohort analysis of plasma metabolites and breast cancer risk - Victoria L. Stevens; Brian D. Carter; Eric J. Jacobs; Marjorie L. McCullough; Lauren R. Teras; Ying Wang (Breast Cancer Research, 2023)
Abstract Background Breast cancer incidence rates have not declined despite an improvement in risk prediction and the identification of modifiable risk factors, suggesting the need to identify novel risk factors and etiological pathways involved in this cancer. Metabolomics has emerged as a promising tool to find circulating metabolites associated with breast cancer risk. Methods Untargeted metabolomic analysis was done on prediagnostic plasma samples from a case–cohort study of 1695 incident breast cancer cases and a 1983 women subcohort drawn from Cancer Prevention Study 3. The associations of 868 named metabolites (per one standard deviation increase) with breast cancer were determined using Prentice-weighted Cox proportional hazards regression modeling. Results A total of 11 metabolites were associated with breast cancer at false discovery rate (FDR) < 0.05 with the majority having inverse association [ranging from RR = 0.85 (95% CI 0.80–0.92) to RR = 0.88 (95% CI 0.82–0.94)] and one having a positive association [RR = 1.14 (95% CI 1.06–1.23)]. An additional 50 metabolites were associated at FDR < 0.20 with inverse associations ranging from RR = 0.88 (95% CI 0.81–0.94) to RR = 0.91 (95% CI 0.85–0.98) and positive associations ranging from RR = 1.13 (95% CI 1.05–1.22) to RR = 1.11 (95% CI 1.02–1.20). Several of these associations validated the findings of previous metabolomic studies. These included findings that several progestogen and androgen steroids were associated with increased risk of breast cancer in postmenopausal women and four phospholipids, and the amino acids glutamine and asparagine were associated with decreased risk of this cancer in pre- and postmenopausal women. Several novel associations were also identified, including a positive association for syringol sulfate, a biomarker for smoked meat, and 3-methylcatechol sulfate and 3-hydroxypyridine glucuronide, which are metabolites of xenobiotics used for the production of pesticides and other products. Conclusions Our study validated previous metabolite findings and identified novel metabolites associated with breast cancer risk, demonstrating the utility of large metabolomic studies to provide new leads for understanding breast cancer etiology. Our novel findings suggest that consumption of smoked meats and exposure to catechol and pyridine should be investigated as potential risk factors for breast cancer.